Analisis Efektivitas Daya Dan Energi Pada Sistem Pembersih Solar PV 2 × 50 Wp dengan Metode Lateral Movement - Malik Al Jabbar, Helmi; Fahmi Hakim, Muhammad (Politeknik Negeri Malang, 2023)
The implementation of the solar cell itself often has problems in its operation. One of the factors that affect the performance of PLTS is that the dirty solar panel cover glass is covered with dust or dirt so that it blocks the intensity of sunlight entering the solar panel which results in a reduced output of the solar panel. A 2x50 Wp solar pv cleaning tool was made to overcome the problem of reduced solar pv output due to the influence of dirt adhering to the pv cover glass. The cleaning tool that has been designed is expected to maximize the quality of power and energy that will be generated by solar pv. The solar pv dirt cleaning tool is used on the research object of the PLTS system in the Renewable Lab, Navy Building, State Polytechnic of Malang. Making a cleaning tool design using Solidworks software, with the reason being able to get a 3D picture of the planned pv dirt cleaner. The cleaning tool works with the help of a battery/power supply as its electrical power. There are 3 dc motors connected to brushes, wheels and water pumps. The cleaning tool moves in a lateral movement (sideways movement) from corner to corner 3 times, then the brush rotates to clean the solar cell cover glass from dirt. In the cleaning process, it can be assisted by using water provided and sprayed by a water pump. The average Vmp and Imp values are 19.72 V and 1.64 A. From the Vmp and Imp values, the average Pmp calculation results are 32.60 W for solar pv after cleaning. Before cleaning, the average maximum voltage (Vmp) and maximum current (Imp) values are 18.43 V and 1.05 A. From the Vmp and Imp values, the average Pmp calculation is 19.65 W.